Decider Life Skills training as a method of promoting resilience with mental health student nurses on clinical placement. (October 2021) - O'Sullivan, Eimear; Gogan, Eimear; Doyle, Louise; Donohue, Gráinne
Abstract: Aim: The aim of this study is to explore mental health student nurses' perceptions and application of a CBT-orientated training programme – the Decider Life Skills programme. Background: The undergraduate nursing degree programme is a challenging one and places high demands both professionally and personally on students. Mental health nursing students are faced with particular stressors including working with people in significant psychological distress, which can result in students feeling overwhelmed and emotionally burdened. There is a requirement for student nurses to be supported to cope with professional and personal difficulties while on practice placement. The Decider Life Skills is a one-day training programme that aims to build resilience and increase effective coping skills. This programme was offered to internship mental health nursing students with the aim of providing them with a toolbox of skills to maintain their wellbeing while on clinical placement. Methods: A qualitative descriptive design was used, and data were collected through two 45-min focus group interviews with mental health students (n = 10) on their internship placement. These students had received a one-day training in Decider Life Skills prior to their clinical placements. Full ethical approval was achieved for this study. Results: Participants reported that they found the skills imparted in the training easy to understand and apply in both their professional and their personal lives. Conclusions: The findings from this study that the Decider Life Skills helped students cope in stressful situations and become more mindful of protecting their own mental health is important, as there is a need to safeguard the emotional well-being of mental health nursing students and support them to become resilient practitioners. Highlights: The Decider Life Skills had a positive influence on participants' clinical placement. The skills were understandable and easily applied professionally and personally. Participants' used skills during their interactions with staff when receiving feedback. Training increased participants' confidence in facilitating service-user groups. Training improved participants' self-care and protection of their mental health.